1994
DOI: 10.1128/jb.176.17.5233-5243.1994
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of an autonomous replication sequence from Coxiella burnetii

Abstract: A Coxiella burnetii chromosomal fragment capable of functioning as an origin for the replication of a kanamycin resistance (Kanr) plasmid was isolated by use of origin search methods utilizing an Escherichia coli host. The 5.8-kb fragment was subcloned into phagemid vectors and was deleted progressively by an exonuclease III-S1 technique. Plasmids containing progressively shorter DNA fragments were then tested for their capability to support replication by transformation of an E. coli polA strain. A minimal au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 63 publications
0
38
0
Order By: Relevance
“…Two-dimensional agarose gel electrophoresis of chromosomal DNA isolated from C. burnetii grown in tissue culture did not reveal DNA replication initiations within ars. It was concluded that, while the C. burnetii ars sequence was not a site for initiation of replication during growth in laboratory hosts, it might function as such in natural hosts (36). This was not the first report of a bacterial ars failing to demonstrate chromosomal origin function.…”
mentioning
confidence: 80%
See 3 more Smart Citations
“…Two-dimensional agarose gel electrophoresis of chromosomal DNA isolated from C. burnetii grown in tissue culture did not reveal DNA replication initiations within ars. It was concluded that, while the C. burnetii ars sequence was not a site for initiation of replication during growth in laboratory hosts, it might function as such in natural hosts (36). This was not the first report of a bacterial ars failing to demonstrate chromosomal origin function.…”
mentioning
confidence: 80%
“…Specific probes were labeled by the incorporation of [␣-32 P]dCTP (Amersham) into DNA by using either oligomer random priming (11) (kit supplied by Boehringer Mannheim), nick translation (31) (kit supplied by Boehringer Mannheim), or PCR (33). PCR-generated probes were labeled by the PCR incorporation of either digoxigenin dUTP (Boehringer Mannheim; reaction conditions as specified by the manufacturer) or [␣- 32 P]dCTP (Amersham) (33,36). The unincorporated nucleotide triphosphates were removed by using Sephadex G-50 spin columns (22).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a plasmid containing a 5.8-kb C. burnetii autonomous replication sequence, they transformed C. burnetii to ampicillin resistance (4,35,36). Transformants exhibited both extrachromosomal replication and integration of the plasmid into the chromosome by homologous recombination.…”
mentioning
confidence: 99%